Talking in All: A Conversation on Poetry and Quakerism Between Philip Gross and Laurence Lerner - Gross, Philip (Quaker studies, 2012)
This considered conversation between two widely published poets of different generations investigates the relationship between their creative work and the Quaker connections in their lives. In the process, both examine examples of their own and each other’s poetry. Drawing on both their academic disciplines, in one case, literary studies, in the other, creative writing, they explore the possible tension between the simple integrity historically advocated by Friends and the imaginative sympathy with diverse experiences required by poetry and fiction. Are the demands of morality compatible with those of aesthetics, and how does eloquence square with plain speaking? In what sense can their writing be seen as Quaker, or themselves as Quaker poets? Lerner starts by asserting that there is no necessary connection between his Quaker and his poet self; Gross finds such a connection in a style of attentiveness, akin to listening. Both recognize the limitations of words to describe deep and complete experience. Poetry, with its pushing of language to the point of breakdown (a process both playful and serious) can point, like Quaker worship, into the wordlessness beyond.